Bundles, stampers, and flying gringos: native perceptions of capitalist violence in Peruvian Amazonia - Santos Granero, Fernando (2010)
In this article we examine a set of stories that have appeared amongthe Ashaninka, Awajun and Wampis of eastern Peru featuring adiversity of white supernatural beings that wander about their communitiesto steal their vital force or introduce harmful substancesinto their bodies, thus affecting their personal and social integrity.We argue that these stories constitute a response to the capitalistviolence experienced by these peoples as a result of hard-linegovernment policies promoting private investment, and the frenziedactivities of a large number of extractive companies. Such stories areinformed by indigenous notions about personhood and illness, butalso by native eco-cosmologies that view life as a scarce resource,the object of intense interspecific competition. If these ‘politicaleconomies of life’ do not turn into a Hobbesian war of all againstall it is due to an ethic of self-regulation that guarantees the balancebetween species despite the practice of generalized predation. Whatdistinguishes this from past junctures of predation by white peopleis that on this occasion native Amazonians feel that the government,in alliance with the extractive companies, has set out to exterminatethem once and for all.